2006
DOI: 10.1177/0149206305277799
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Leadership Style and Team Process on Performance and Innovation in Functionally Heterogeneous Teams

Abstract: This study focused on leadership style (participative leadership/directive leadership) as a key factor, which has an intervening impact on a functionally heterogeneous team’s process and outcomes. In a study of 136 primary care teams, the author found that in high functionally heterogeneous teams, participative leadership style was positively associated with team reflection, which in turn fostered team innovation; however, this leadership style decreased team in-role performance. The impact of directive leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
358
3
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 416 publications
(390 citation statements)
references
References 72 publications
16
358
3
13
Order By: Relevance
“…In models 1 and 2, in which the measure of participative leadership appears, its coefficient is different from 0 at levels of significance of 95%. This evidence clearly supports Hypothesis 2 in the line of research by King and Anderson (1990), Somech (2006), andWoodman et al (1993), who associate collaboration, free exchange of information, and the process of reflection with the innovative process.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In models 1 and 2, in which the measure of participative leadership appears, its coefficient is different from 0 at levels of significance of 95%. This evidence clearly supports Hypothesis 2 in the line of research by King and Anderson (1990), Somech (2006), andWoodman et al (1993), who associate collaboration, free exchange of information, and the process of reflection with the innovative process.…”
Section: Resultssupporting
confidence: 84%
“…In this sense, other authors find that democratic and collaborative leadership increases the probability of creative outcomes (King and Anderson 1990;Woodman et al 1993). Also, the literature suggests that the free exchange of information is crucial for creativity and innovation (Amabile 1988;King and Anderson 1990;Woodman et al 1993) and that the process of reflection has an influence on innovation (Somech 2006) through the identification of problems and the production of creative solutions. Krause (2004) finds that granting degrees of freedom and autonomy is positively related to the generation and testing of ideas.…”
Section: Conceptual Framework and Hypotheses Proposedmentioning
confidence: 96%
“…As in other research on work teams (Alper et al, 2000;Cohen & Ledford, 1994;Somech, 2006), in this study as well obtaining objective work outcome measures proved impossible, despite the willingness of the organization to provide such measures. The companies did not collect team-level productivity data.…”
Section: Team Performancementioning
confidence: 79%
“…They found that psychological empowerment was a significant mediator of the relationship between structural empowerment and creativity, and that both structural and psychological empowerment were mediators of the relationship between transformational leadership and creativity. Somech (2006) also found that participative leadership had a strong positive effect on team innovation and that team reflection was an important mediator. These findings are of interest, however, the construct of authentic leadership has been criticized for its broad definitions its possible overlap with other positive forms of leadership such as transformational and ethical leadership, its loose interpretation of the philosophical works that are used as its theoretical foundation, such as Heidegger's (1962) notion of "resoluteness", as well as its favoring a collective self at the expense of the individual self and subjectivity.…”
Section: Behavioral Perspectivesmentioning
confidence: 86%